The clash of capitalisms : Chinese companies in the United States / Ji Li, Rutgers University School of Law. - Li, Ji, 1976- (Cambridge University Press, 2018)
Chinese foreign direct investment in the United States has generated intense debates. Some welcome it for the immediate benefits such as job creation; others view Chinese investments, especially those controlled by the Chinese government, as a critical threat. The debates have so far missed an important question: how do Chinese companies investing in the US react to the host country's law? Ji Li formulates a novel analytical framework to examine the adaptation of Chinese companies to general US institutions and their compliance with US laws governing tax, employment equality, and national security review of foreign investments. The level of compliance varies, and this variation is examined in relation to company ownership, including state ownership. Li's analysis is based on interviews and a unique and comprehensive dataset about Chinese companies in the United States that has never been systematically explored.